2010
DOI: 10.1080/14616734.2010.501988
|View full text |Cite
|
Sign up to set email alerts
|

Reflective functioning in mothers with drug use disorders: Implications for dyadic interactions with infants and toddlers

Abstract: In this study, we examined maternal reflective functioning as a bi-dimensional construct in a sample of 47 mothers with drug use disorders and caring for infants and toddlers. We first tested a two-factor solution with scale items from the Parent Development Interview and confirmed the presence of two related but distinct dimensions – self-mentalization and child-mentalization. We then tested predictions that (a) self-mentalization would be associated with overall quality of maternal caregiving and that (b) ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
224
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 183 publications
(246 citation statements)
references
References 23 publications
20
224
1
1
Order By: Relevance
“…Reflective functioning is generally low in SA parents as they struggle to separate their feelings of anger towards their situation from anger towards their child (Borelli et al, 2012). Such parents are more likely to attribute negative intentionality towards their children and respond with hostility (Dunn et al, 2002; Suchman, DeCoste, Leigh et al, 2010). Lack of emotional regulation combined with drug states limit parents’ abilities to focus on alternative explanations for their children’s negative behavior or anticipate the negative consequences of their own violent reactions (Kelley, 1998; Jansson & Velez, 1999; Miller et al, 1999).…”
Section: Pathways Of Influence Linking Substance Abuse and Child Maltmentioning
confidence: 99%
See 2 more Smart Citations
“…Reflective functioning is generally low in SA parents as they struggle to separate their feelings of anger towards their situation from anger towards their child (Borelli et al, 2012). Such parents are more likely to attribute negative intentionality towards their children and respond with hostility (Dunn et al, 2002; Suchman, DeCoste, Leigh et al, 2010). Lack of emotional regulation combined with drug states limit parents’ abilities to focus on alternative explanations for their children’s negative behavior or anticipate the negative consequences of their own violent reactions (Kelley, 1998; Jansson & Velez, 1999; Miller et al, 1999).…”
Section: Pathways Of Influence Linking Substance Abuse and Child Maltmentioning
confidence: 99%
“…Studies have shown that parents with SA spend less time interacting with their children (Clausen et al, 2012; Suchman, De Cosete, Leigh et al, 2010), report lower levels of satisfaction in their parental relationships (Lussier et al, 2010), initiate fewer interactions with their children in behavioral observation paradigms (Pajulo et al, 2006) and exhibit diminished bonding behaviors towards their children starting in infancy (Dunn et al, 2002). Furthermore, when mother-child dyads do interact, their exchanges are characterized by less enthusiasm or mutual enjoyment, and more conflict (Pajulo et al).…”
Section: Pathways Of Influence Linking Substance Abuse and Child Maltmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of PRF measures has expanded to different contexts such as drug-use disorders [25], mothers with childhood maltreatment [26,27], infant distress [28], and parenting programs [12,[29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most relevant findings was the high rate of absence in the prenatal care of the users (75%), as well as the high rate of infectious diseases. Our data highlights the need for a more active process in the engagement of this special population in both prenatal care and drug treatment, favoring post-partum conditions, such as trying to avoid motherbaby separation, stimulating breast feeding, in order to build secure attachment 15 . This approach, rarely offered by public health care worldwide, could help to promote primary prevention in childhood.…”
Section: Discussionmentioning
confidence: 99%